Organization Theory for Implementation Science (OTIS): reflections and recommendations - Birken, Sarah A.; Baloh, Jure; Kegler, Michelle C.; Huang, Terry T.-K.; Lee, Matthew; Adsul, Prajakta; Ryan, Grace; Peluso, Alexandra; Wagi, Cheyenne; Randazzo, Aliza; Mullins, Megan A.; Morrill, Kristin E.; et al. (Frontiers in Health Services, 2024)
Organizations exert influence on the implementation of evidence-based practices and other innovations that are independent of the influence of organizations' individual constituents. Despite their influence, nuanced explanations of organizations' influence remain limited in implementation science. Organization theories are uniquely suited to offer insights and explain organizational influences on implementation. In this paper, we describe the efforts of the Cancer Prevention and Control Research Network's (CPCRN) Organization Theory for Implementation Science (OTIS) workgroup to equip implementation scientists with theory-guided understanding of organizational influences on implementation. We provide a set of recommendations for future efforts to enhance implementation through the use of organization theories and OTIS tools.